Association between substance use, family conflict, anger and depressed mood among Icelandic high school students - Telma Jónsdóttir 1994- (2019)
The consumption of alcohol and illegal is one of the leading risk factors worldwide for disability and premature death. Adolescence is a critical time because that is when many start to develop problems or risky behaviors, such as substance use. The aim of this study was to examine the association between family conflict, anger, depressed mood and substance use among Icelandic adolescents. In addition, to examine gender differences of adolescents’ substance use and to test whether anger and depressed mood mediated the relationship between family conflict and substance use. The current study used data from a larger study conducted by the Icelandic Centre for Social Research and Analysis (ICSRA) called Youth in Iceland 2016. The participants consisted of 2024 high school students, at the age 14 to 21 years old. The results revealed that girls were more likely to consume alcohol, while boys were more likely to consume marijuana. The results also revealed that family conflict increased the likelihood on consuming both alcohol and marijuana directly and through the mediators, anger and depressed mood. Keywords: substance use, family conflict, anger, depressed mood, adolescents Neysla áfengis og ólöglegra fíkniefna er ein helsta orsök sjúkdóma og dauðsfalla um allan heim. Unglingsárin eru mikilvægur tími þar sem þá byrja margir að neyta vímuefna og eiga í hættu á að þróa með sér vandamálanotkun. Tilgangur þessarar rannsóknar var að kanna sambandið á milli fjölskylduágreinings, reiðis, leiðis og vímuefnanotkunar meðal íslenskra ungmenna. Þar að auki að skoða hvort kynjamunur vímuefnanotkunar meðal ungmenna liggi fyrir. Einnig var rannsakað hvort reiði og leiði miðli sambandinu milli fjölskylduágreinings og vímuefnanotkunar. Notast var við gögn frá Rannsóknir & Greining (R&G) úr spurningalistanum “Ungt fólk 2016”. Þátttakendurnir samanstóðu af 2024 framhaldsskólanemum, á aldursárunum 14 til 21 árs. Niðurstöðurnar sýndu fram á að stelpur væru líklegri til að neyta áfengis en hins vegar að strákar væru líklegri ...